MORPHOHISTOLOGICAL CHARACTERISTICS OF THE HEART, LIVER AND KIDNEYS UNDER THE INFLUENCE OF DOXORUBICIN AND METABOLIC DRUGS - Kuchmenko, O.B.; Dziuba, V.O.; Savosko, S.I.; Kozytska, T.V.; Kvasko, O.Yu.; Gumenyuk, A.V.; Oliinyk, T.M. (World of Medicine and Biology, 2020)
Doxorubicin is one of the most effective drugs, which is often used in clinical practice. The purpose of this work was to study the structural basis of the doxorubicin toxic effects on the heart, liver and kidneys and under the influence of metabolic drugs. Results of the histological and morphometric studies indicate the potential cytoprotective properties of the studied metabolic drugs – ubiquinone-10, a complex of precursors and modulator of ubiquinone biosynthesis (vitamin E, methionine, paraoxybenzoic acid and magnesium) and tiotriazolini in the conditions of experimental doxorubicin cardiomyopathy (the cumulative dose of doxorubicin is 15 mg/kg) and can serve as an experimental justification for their feasibility as a protective agents in clinical practice.
Keywords: doxorubicin; heart; liver; kidney; ubiquinone; thiotriazolini